Corrosion. - Shreir, L. L.; Burstein, G. T.; Jarman, R. A. (Butterworth-Heinemann, 1994)
This book provides an encyclopedic coverage of corrosion science and technology. It is a reference work embracing topics including high-temperature and aqueous corrosion and their control.